Implementasi Program Rehabilitasi Sosial bagi Penyandang Disabilitas Miskin di Kabupaten Aceh Barat - Munawarah, Munawarah; Afriandi, Fadli (Kolaborasi : Jurnal Administrasi Publik, 2025)
Social rehabilitation for persons with disabilities serves as anessential strategy to expand access to basic rights and economic participation. This study examines how such a program is carried out in West Aceh by applying Edward III’s implementation perspective, emphasizing communication, resources, disposition, and bureaucratic structure. A qualitative descriptive approach was used through interviews, observations, and document review involving implementing officials and recipients of assistance. The results show that program execution generally aligns with formal procedures, yet communication between the Social Service Office and field facilitators remains uneven. Resource allocation is still constrained, particularly in staffing capacity, budget availability, and logistical support. Implementers tend to demonstrate supportive attitudes, but the outcomes of assistance vary, with assistive equipment yielding more sustained benefits than short-term food support. The bureaucratic mechanism also faces fragmentation, limiting coordination across agencies. Overall, the social rehabilitation initiative in West Aceh represents progress, though further refinement in communication flow, resource strengthening, professional competence, and inter-institutional synergy is required to enhance program consistency and long-term effectiveness.